A double-chamber energy storage device with dual ionic electrolyte enabling high energy density. (1st June 2018) - Guo, Fen; Li, Yiju; Cao, Dianxue; Fan, Baoan; Liu, Yi; Lu, Lilin; Lei, Yang
Abstract: In this work, for the first time, we design a high-energy-density double-chamber capacitor which consists of the cathode chamber (polyaniline@carbon fiber cloth electrode in HCl/FeCl3 solution), anion-exchange membrane and the anode chamber (polyaniline@carbon fiber cloth electrode in HCl/FeCl2 solution). Since the redox state of polyaniline can be continuously altered by the external potential during charging and discharging process, the addition of FeCl3 (or FeCl2 ) in the electrolyte works as chemical oxidant (or reductant) to oxidize (or reduce) the reduced (or oxidized) polyaniline to offer extended capacitance. Results show the double-chamber supercapacitor has a high area specific capacitance of 1.22 F cm −2 and an energy density of 108.44 μWh cm −2, which are ∼3.5 times as large as those of the conventional single-chamber capacitor (0.35 F cm −2 / 31.11 μWh cm −2 ). This work demonstrates an innovative strategy by incorporating supercapacitor with fuel cell to improve the energy density. Graphical abstract: Image 1 Highlights: A double-chamber supercapacitor with dual ionic electrolyte was designed. The double-chamber supercapacitor is the combination of fuel cell and supercapacitor. FeCl3 and FeCl2 additions contribute to the enhancement of energy density. The energy density is increased to 3.5 times as compared with the conventional one.